ER to synapse trafficking of NMDA receptors - Horak, Martin; Petralia, Ronald S.; Kaniakova, Martina; Sans, Nathalie (Frontiers in Cellular Neuroscience, 2014)
Glutamate is the major excitatory neurotransmitter in the mammalian central nervous system. There are three distinct subtypes of ionotropic glutamate receptors that have been identified including 2-amino-3-(5-methyl-3-oxo-1,2-oxazol-4-yl)propanoic acid receptors (AMPARs), N-methyl-D-aspartate receptors (NMDARs) and kainate receptors. The most common glutamate receptors in mature synapses are AMPARs that mediate the fast excitatory neurotransmission and NMDARs that mediate the slow excitatory neurotransmission. There have been large numbers of recent reports studying how a single neuron regulates synaptic numbers and types of AMPARs and NMDARs. Our current research is centered primarily on NMDARs and, therefore, we will focus in this review on recent knowledge of molecular mechanisms occurring 1) early in the biosynthetic pathway of NMDARs, 2) in the transport of NMDARs after their release from the endoplasmic reticulum, and 3) at the plasma membrane including excitatory synapses. Because a growing body of evidence also indicates that abnormalities in NMDAR functioning are associated with a number of human psychiatric and neurological diseases, this review together with other chapters in this issue may help to enhance research and to gain further knowledge of normal synaptic physiology as well as of the etiology of many human brain diseases.